Tilapia Culture. - Junio, Gobleth D. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1980)
The growing population of our country threatens our food resources. Year to year, the number of mouths to be fed increases and yet, our land area and our water area remain the same. Farm lands as well as our bodies of water, where our find is high, but the supply scarce. As a result, commodities are high priced, and fish is one. To resolve the growing food problem of our country, we have to increase our food resources. The fishing industry is one solution. This does not mean however, that we have to overfish our rivers, lake sand seas to get so much fish for our market. Instead we have to further develop the old practices of pond fish culture and still look for more practical ways on how we can raise more fish. Our government therefore encourages the culture of fish to raise a maximum production encourages the culture of fish to raise a maximum production and thereby maintaining its supply to satisfy our people's requirements. With about 500, 000 hectares of brackish water swamplands, 900, 000 ha. Of freshwater areas and approximately 16, 000, 000 ha. Of marine waters, our task of raising fish is not too hard for us. Some of these are not yet well developed and they await the time when fish are raised for production and human consumption. It is therefor the object of this report to share the culture methods of one on the most raised freshwater fish. The tilapia, in answer to our effort food production.
Keywords: Fish-culture.